Mystery Road. Series 1 [videorecording (DVD)] - Pedersen, Aaron, 1970-; Davis, Judy, 1956-; Mailman, Deborah; Blair, Wayne, 1971- (Acorn, 2019)
When two boys disappear from a remote cattle station, local police sergeant Emma James calls in Indigenous detective Jay Swan to help find out what happened. As Emma and Jay butt heads over their conflicting methods, the unexpected arrival of Jay's troubled daughter only inflames the tension. But when their investigation uncovers other crimes haunting the backwater town, the detectives must look to the past to get justice in the present.